In-Facility Infant Feeding and Discharge Practices for Moderately Low Birthweight Newborns in 12 Hospitals Across India, Malawi, and Tanzania. (14th June 2022) - Mokhtar, Rana; Semrau, Katherine; Bellad, Roopa; Dhaded, Sangappa; Guruprasad, Gowdar; Mvalo, Tisungane; Phiri, Melda; Saidi, Friday; Manji, Karim; Salim, Nahya; Sudfeld, Christopher
Abstract: Objectives: Globally, rates of facility-based childbirth have increased, enabling early intervention for vulnerable newborns. We describe health system-level inputs, current feeding practices, and discharge practices for moderately low birthweight (MLBW) infants (1500 to < 2500 g) in four resource-constrained settings. Methods: The Low Birthweight Infant Feeding Exploration study is a mixed methods observational study in 12 secondary- and tertiary-level facilities in four sites in India, Malawi, and Tanzania. We analyzed data from facility assessments and a prospective observational cohort of 148 MLBW infants from birth to facility discharge. Results: Across the 12 facilities, availability of key equipment and supplies was variable. Anthropometric measuring equipment such as head circumference tapes was present in 8 out of 12 facilities and length boards in 7/12. Key medications were limited including surfactant (3/12) and parenteral nutrition (1/12). Feeding supports like milk expression tools were available in all 12 sites, but human milk alternatives (e.g., donor milk (1/12), formula (6/12)) was more limited. Infants were preterm appropriate/large-for-gestational age (41.9%), preterm small-for-gestational age (SGA) (11.5%), and term SGA (46.6%). Median length of stay was 3.1 days (IQR: 1.5, 5.7); 32.4% of infants were NICU-admitted and 67.6% were separated from mothers during admission. Health facilities successfully promoted exclusive breastfeeding with 93.2% of infants exclusively breastfed. Group lactation support was provided, albeit not universally. 81.8% of mother-infant dyads received 1 support session; 56.1% received 2 + support sessions. At discharge, 18.8% of infants were below the facility based weight policy minimum (1500g or 1800g) and 5.1% of all infants had lost more than 10% of their birthweight. Conclusions: Constrained health system inputs hinder provision of high quality care for MLBW infants. Targeted lactation support specific to LBW infants, and appropriate access to feeding alternatives are necessary to position MLBW infants for successful feeding and growth post-discharge. Funding Sources: Bill & Melinda Gates Foundation.